Efficacy of Chitosan as Pb Remover and its Effect on Zebrafish (Danio rerio) Embryo Development - K. Nirmala; J. Sekarsari; P. Suptijah (Jurnal Akuakultur Indonesia)
Chitosan is a by-product from crustacean carapas. Chitosan has a cationic  polyelectrolyte activity, hence it can be used as remover of heavy metal from polluted water.  This study was aimed to determine optimum concentration of chitosan to remove Pb, efficacy time in Pb removal and its effect on early development of zebrafish (Danio rerio) embryos.  The treatments in this study was control, and chitosan concentration of 70, 85 and 100 mg/L. the results of this study showed that maximum reducing of Pb was obtained at the time of 48 and 72 hours after treatment by chitosan, but Pb level was returning to increase after 96 hours of chitosan treatment.  Abnormality of zebrafish embryos and survival rate of larvae were similar (p>0.05) among treatments, while hatching rate in 100 g/L chitosan was significantly different  (p≤0.05).  Thus, chitosan in concentration of 85 mg/L was effective to  remove Pb  till  81.12% for 3 days, and could increased hatching rate till 59.75%.